The update of the native administrative legislature in the sphere of anti-corruption - Гончарук, Степан Тихонович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
Theoretical legal norms of a new anticorruption legislature of Ukraine are explored. Corruption in the late twentieth and early twenty-first century has become one of the most dangerous and threatening social phenomena in the world. To overcome this threat in our society various state and public institutions are involved. Among other things, an effective fight against corruption in the country is possible only if there is proper anti-corruption legislation, which is gradually improving in Ukraine. For some period of time national legislature concerning preventing and combating corruption was passive. There was even no legal definition of «corruption offence». Only on October, 15, 1995 the Law of Ukraine «On combating corruption» was enacted. The Code of administrative offences of Ukraine was amended; a new chapter «Administrative corruption offences» was added. Appropriate changes were added to the Criminal Code of Ukraine as well. The term «corruption» could be understood as a usage by certain, defined in the law, persons of their authority and possibilities on the purpose to get illegal benefit or receiving a promise/offer of such benefit for themselves or other persons or respectively promise/offer or provision of illegal benefit to the persons mentioned above to make them use their powers and opportunities illegally. In the same time radical social and political changes of 2014 year led to the renewal of national anticorruption legislature. October, 14, 2014 a list of new anticorruption laws was enacted. Among them: «On prevention of corruption», «On National anticorruption bureau». New law excluded responsibility for the corruption offences. Together with other important social and political factors of the corruption resistance mechanism in our country a new anticorruption legislature must become an essential part of this mechanism on the purpose to overcome this shameful phenomenon.